LITERASI ASESMEN: BEKAL GURU UNTUK PENINGKATAN KUALITAS PEMBELAJARAN DI SEKOLAH - Sari, Murni Sapta; Setiawan, Deny; Alifiani, Alifiani (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2024)
The existence of a teacher-producer college must have an effect on surrounding schools. Assessment literacy is needed by teachers through authentic assessment to optimize learning in the classroom. The problem of partners related to assessment literacy is in compiling assessments of the planning stage and implementation of learning that is still inappropriate. The objectives of the implementation of this service are as follows: To optimize assessment literacy in learning and to assist Teachers members of the Biology MGMP of SMA in Blitar region in compiling authentic assessments in Biology learning in accordance with the Independent Curriculum. The implementation of activities was carried out at Talun Blitar State High School.The training method in this activity uses the Participatory Training Model. Based on the results of the Teacher Response Percentage, it can be shown that a positive response was obtained from MGMP teachers in the Blitar region. The teachers showed enthusiasm in carrying out literacy assessment assistance activities. Teachers find it helpful to provide mentoring activities to improve the quality of learning in schools Keywords: literacy assessment, quality of learning, in schools